A poética do trágico na estrutura narrativa pós-colonial de Mia Couto - Aline Camara Zampieri (2019)
The purpose of this thesis is to demonstrate through the analysis and interpretation of identity, social, ideological and historical-cultural contours outlined in the narrative A river called time, by the Mozambican writer Mia Couto, the presence of the tragic and how it intertwines with the narrative elements of the work, beyond shows how these foundations are permeated in the construction of the author's aesthetic-political project. This research has like reference the cultural and ideological horizon of the period in which the narrative was produced and is based on already existing readings, evidencing that the fecundity of literary creation is generally related to the most intense historical moments, thus inscribed in the framework of Comparative Literature. We see, indeed, a rich literature in sacred images which retake both the hegemonic tradition and the traditions of the native peoples from Mozambique in the Mia Couto’s work. These images that refer to the hybridity of a postcolonial literature are analyzed in this research from the notions of the tragic proposed by Aristóteles (2005), Peter Szondi (2004), Nietzsche (2013), Raymond Williams (2002) among others, with the objective of reflect about the construction process of a new literary / social / cultural identity that has been proposed by the Mozambican writer in relation to his country. The conceptions of de Homi K. Bhabha (2013), Stuart Hall (2011) and Thomas Bonnici (2009) about the cultural aspects resulting of colonization and post-colonization processes will also be introduced in this work. In addition we allude to the works of the literary tradition and The life of a South African tribe by Henrique Junod in order to mark the mixture of these cultures in the formation of this new Mozambican identity. Thus the present thesis is divided in four chapters: in the first "Mar, sargaço mar: das grandes navegações ao discurso pós-colonial (Sea, sargasso sea: from the great navigations to the postcolonial discourse" is called in the history of Mozambique marked by the Portuguese colonization, by reflections on the postcolonialism, diaspora and multiculturalism. The second one “Da literatura moçambicana a Um rio chamado tempo, uma casa chamada terra (From Mozambican literature to A river called time)” brings some deliberations about the romance based on considerations on Mozambican Literature, aspects of Mia Couto’s life as well as his aesthetic design. We will discuss aspects of the tragic presence in the diegetic construction of some Mia Couto’s short stories as from questions related to the tragic since the Greek thought until the contemporaneity in the third chapter named “Do nascimento da tragédia ao trágico na literatura contemporânea (From the tragic’s born to the tragic in the contemporary literature)”. The fourth chapter named “Os elementos trágicos na construção narrativa de Um rio chamado tempo, uma casa chamada terra (The tragic elements in the narrative construction of A river called time)” analyzes the narrative construction of the romance and how they are connected to the tragic conceptions studied in the third chapter, especially of the modern tragic though in addition to discussions on the post-colonialism, whether either as marks of a hybrid culture or as the search for a (new) Mozambican identity.